Applications of Artificial Intelligence in Tribology - Ji, Yangyang; Bao, Jiusheng; Yin, Yan; Ma, Chi (Recent Patents on Mechanical Engineering, 2016)
Background: Tribological system is a complex nonlinear system. In recent years, for outstanding ability of analyzing nonlinear problems, the Artificial Intelligence (AI) has been widely applied in tribology. Objective: The purpose of this study is to provide an overview of AI and its developments, and to introduce and analyze how AI technologies are applied to solve complex nonlinear tribological problems. Methods: In this study, the applications of AI in tribology were analyzed from three aspects: design of tribological systems, development of friction materials, and monitoring and diagnosis of friction and wear behaviors. The research methods and progress of AI in tribology were summarized as follows: design tribological system; design and optimize formula of friction materials; analyze typical tribological performance parameters such as friction coefficient, friction heat and wear rate; monitor and diagnose friction states and wear forms. Results: In order to improve the efficiency and effectiveness of AI in solving tribological problems, current development and applications of AI in tribology are provided specifically. Conclusion: AI technologies are greatly beneficial to solve complex and nonlinear tribological problems. Owing to that various AI technologies have their advantages and shortcomings, combinations of different AI technologies must be more effective in solving tribological problems. In this article, various patents have been discussed.
Keywords: friction material